Pious way to politics: the rise of political Salafism in post-Mubarak Egypt - al-Anani, Khalil; Malik, Maszlee (WILEY PERIODICAL,USA, 2013)
The Arab Spring has reshaped the Islamist landscape in the Middle East drastically. After decades of repression and exclusion, Islamist parties have taken power in Egypt, Tunis, and Morocco. However, the startling rise of Salafism (Salafiyya) remains the most visible feature of the new Islamist scene in the region. After decades of eschewing politics for theological and political reasons, Salafi movements and groups have rushed into electoral politics enthusiastically. They became keen to form political parties, contest elections, and vie for power. In Egypt, the Salafi parties fared well in the post-revolution parliamentary elections and are a key player in drafting Egypt’s new constitution. This article explores the rise of Salafism after Mubarak and examines its effects on the democratic transition in Egypt. It investigates the ideological and theological stance of Salafi movements and parties on politics and democracy in particular. The argument put forward is that the extraordinary political openness in Egypt after the revolution has pushed Salafis into everyday politics. Subsequently, Salafis have become more inclined to adopt a pragmatic and practical discourse. Based on field research, this article provides a thematic analysis of Egyptian Salafism and assesses its political future.